The Toyota Way: 14 Management Principles from the World's Greatest Manufacturer - and Liker, Jeffrey K. (McGraw-Hill, 2004)
How to speed up business processes, improve quality, and cut costs in any industryIn factories around the world, Toyota consistently makes the highest-quality cars with the fewest defects of any competing manufacturer, while using fewer man-hours, less on-hand inventory, and half the floor space of its competitors. The Toyota Way is the first book for a general audience that explains the management principles and business philosophy behind Toyota's worldwide reputation for quality and reliability.Complete with profiles of organizations that have successfully adopted Toyota's principles, this book shows managers in every industry how to improve business processes by:Eliminating wasted time and resources Building quality into workplace systems Finding low-cost but reliable alternatives to expensive new technology Producing in small quantities Turning every employee into a quality control inspector